2015
DOI: 10.3233/jad-150080
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric and Shape Analysis of the Thalamus and Striatum in Amnestic Mild Cognitive Impairment

Abstract: Alterations in brain structures, including progressive neurodegeneration, are a hallmark in patients with Alzheimer's disease (AD). However, pathological mechanisms, such as the accumulation of amyloid and the proliferation of tau, are thought to begin years, even decades, before the initial clinical manifestations of AD. In this study, we compare the brain anatomy of amnestic mild cognitive impairment patients (aMCI, n = 16) to healthy subjects (CS, n = 22) using cortical thickness, subcortical volume, and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 76 publications
2
16
0
Order By: Relevance
“…The contractions found in the pulvinar and dorsal aspects of the VP in MCI-CB are consistent with contractions that have been identified in amnestic MCI by an earlier study of our group (Leh et al, 2015). Additionally, the authors have documented contractions in regions that remained unaffected in the present MCI-CB sample such as the VL and lateral posterior nuclei.…”
Section: Discussionsupporting
confidence: 92%
“…The contractions found in the pulvinar and dorsal aspects of the VP in MCI-CB are consistent with contractions that have been identified in amnestic MCI by an earlier study of our group (Leh et al, 2015). Additionally, the authors have documented contractions in regions that remained unaffected in the present MCI-CB sample such as the VL and lateral posterior nuclei.…”
Section: Discussionsupporting
confidence: 92%
“…Unlike our previous analyses using subcortical overall volumes, we found that subcortical regional PiB retention values were associated with the surface of the bilateral hippocampus and thalamus and the right pallidum. Surface displacement associated with hippocampal Aβ owed exclusively to local volume changes; these changes were located bilaterally in regions roughly corresponding to the CA1 subfield and subiculum and were more prominent in the left hippocampus, which is in line with previous shape-based investigations in AD and MCI patients reporting abnormal surface in the hippocampus (Csernansky et al, 2000;Leh et al, 2016;Lindberg et al, 2012). Lateral deformation of the hippocampus, which we also found in our study, was reported to predict cognitive decline and dementia onset in cognitively normal individuals (Csernansky et al, 2005;Zanchi, Giannakopoulos, Borgwardt, Rodriguez, & Haller, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…A vertex‐based surface approach was used to investigate Aβ‐associated local surface changes in subcortical structures and whether these changes related more to local volume or shape. Surface‐based approaches have proven efficient in the detection of subtle surface abnormalities in subcortical structures in AD, MCI, and cognitively normal individuals (Csernansky et al, ; de Flores et al, ; Kalin et al, ; Leh et al, ; Schroeder et al, ). Unlike our previous analyses using subcortical overall volumes, we found that subcortical regional PiB retention values were associated with the surface of the bilateral hippocampus and thalamus and the right pallidum.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we performed a linear regression of the right pulvinar (rPul) volume and years consuming cocaine, with total brain volume, age and sex as covariates. A liberal FDR threshold was chosen due to the small sample size, the high variability of results in previous studies, and consistency with previous reports on shape analysis 38,44 . For visualization purposes only, we created corrected volume variables using the residuals of the linear model.…”
Section: Discussionmentioning
confidence: 85%